Virtual Learning Environment to Support Object Oriented Programming Learning - Angarita, Adriana M.; Guerrero, Cesar D.; Perera, Graciela (Revista Colombiana de Computación, 2012)
Object-oriented programming is one of the core programming paradigms taught in introductory programming courses in engineering.